A contingent‐claim integration of cost‐volume‐profit analysis with capital budgeting* - CHEUNG, JOSEPH K.; HEANEY, JOHN (Contemporary Accounting Research, 1990)
Abstract. This paper integrates cost‐volume‐profit (CVP) analysis into the theory of capital budgeting by modeling the profit function in the CVP relation as put and call options on sales revenue. Such an approach is shown to be particularly useful when the profit function is piecewise linear, such as when there are multiple break‐even points, or when the profit function is truncated. The results are of general applicability because such an approach does not require making assumptions about the decision maker's risk attitude. This claim is proven by showing that certain well‐known decision models in the extant literature can be derived as specific cases from the results. The paper also shows how the CVP analysis can be extended to the case in which there is a dependence of the firm's cash flows on macroeconomic variables. Specifically, it applies to the CVP analysis the state‐contingent claim approach to capital budgeting of Banz‐Miller (1978) and relates the option valuation approach to Banz and Miller's framework. A numerical example using the state prices of Banz‐Miller is provided. Résumé. Les auteurs associent l'analyse coût‐volume‐profit (CVP) à la théorie de l'établissement du budget des investissements en intégrant la fonction de profit dans l'interaction CVP à titre d'option de vente et d'achat sur le produit des ventes. Cette methode semble particulièrement utile lorsque la fonction de profit est linéaire mais morcelée. Il en ainsi, par exemple, lorsqu'il existe plusieurs seuils de rentabilité ou lorsque la fonction de profit est tronquee. Les résultats peuvent êtres généralisés puisqu'une méthode de ce genre n'exige pas la formulation d'hypothèses relatives à l'attitude du décideur à l'egard du risque. Cette affirmation est étayée par les auteurs qui montrent que certains modèles décisionnels bien connus dans la documentation existante peuvent être dérivés des résultats obtenus sous forme de cas précis. Les auteurs montrent également comment l'analyse coût‐volume‐profit peut être étendue au cas où les flux monétaires de l'entreprise dépendent de variables macroéconomiques. De façon précise, ils appliquent à l'analyse coût‐volume‐profit la méthode des créances conditionnelles à un état proposée par Banz et Miller pour établir le budget des investissements, et ils relient la méthode d'évaluation de l'option à la formule de Banz et Miller. Les auteurs proposent un exemple numérique dans lequel ils recourent aux prix de l'état de Banz‐Miller.